2013
DOI: 10.1007/s00422-013-0569-z
|View full text |Cite
|
Sign up to set email alerts
|

A computational theory of visual receptive fields

Abstract: A receptive field constitutes a region in the visual field where a visual cell or a visual operator responds to visual stimuli. This paper presents a theory for what types of receptive field profiles can be regarded as natural for an idealized vision system, given a set of structural requirements on the first stages of visual processing that reflect symmetry properties of the surrounding world. These symmetry properties include (i) covariance properties under scale changes, affine image deformations, and Galil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(163 citation statements)
references
References 177 publications
(373 reference statements)
7
155
0
1
Order By: Relevance
“…Let us assume a (i) perspective camera model extended with (ii) a thin circular lens for gathering incoming light from different directions and (iii) a Lambertian illumination model extended with (iv) a spatially varying albedo factor for modelling the light that is reflects from surface patterns in the world. Then, it can be shown (Lindeberg [106,Sect. 2.3]) that a spatial receptive field response…”
Section: Extension To Illumination Invariancementioning
confidence: 99%
See 1 more Smart Citation
“…Let us assume a (i) perspective camera model extended with (ii) a thin circular lens for gathering incoming light from different directions and (iii) a Lambertian illumination model extended with (iv) a spatially varying albedo factor for modelling the light that is reflects from surface patterns in the world. Then, it can be shown (Lindeberg [106,Sect. 2.3]) that a spatial receptive field response…”
Section: Extension To Illumination Invariancementioning
confidence: 99%
“…A general theoretical framework for how local receptive field responses, as used in the SIFT and SURF descriptors and their extensions or analogues to colour images and spatiotemporal image data, can constitute the basis for computing inherent properties of objects to support invariant recognition under natural image transformations is presented in (Lindeberg [106,109]) including relations to receptive fields in biological vision.…”
Section: Related Workmentioning
confidence: 99%
“…Based on this spatio-temporal receptive field model, we define a spatio-temporal scale-space representation of the form [67,69,75] …”
Section: Spatio-temporal Receptive Field Modelmentioning
confidence: 99%
“…Cell recordings from neurones in the primary visual cortex have shown that there are spatio-temporal receptive fields tuned to different sizes and orientations in the image domain, to different integration times over the temporal domain as well as to different image velocities in space-time [12,13,32,33]. Interestingly, the shapes of the spatio-temporal receptive field families that have been measured in biological vision can furthermore be explained by normative theories of visual receptive fields [69,71,75,78], whose axiomatic derivation is based on structural properties of the environment in combination with assumptions about the internal structure of an idealized vision system to ensure a consistent treatment of image representations over multiple spatio-temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Such a framework then leads to Gaussian-related kernels characterizing any linear visual system including early biological visual systems when they behave linearly (see e.g. Weickert et al 1999;Lindeberg 2011;Lindeberg 2013;ter Haar Romeny et al 2001;ter Haar Romeny 2003;Koenderink 1988;Florack 1997). On the other hand, a model based on the anatomical and physiological properties of biological visual systems is proposed in (Mahmoodi 2015) to derive Gaussian-related kernels in spatial as well as spatio-temporal domains.…”
Section: Introductionmentioning
confidence: 99%